Credible commitments in contract relations: Where are the limits of the possible? - Andrey E. Shastitko (Управленец, 2022)
Credible commitments are the most important condition for contracts sustainability. The effects and ways of ensuring the commitments credibility are discussed in the new institutional economics and game theory. At the same time, there is a number of unresolved issues related to the microeconomic aspects of obligations’ reliability in contracts regarding specific resources. The article delves into various approaches to determining credible commitments in contractual relations at the micro level in the context of bilateral (multilateral) opportunism. The methodological basis of the study is the transaction costs economics. The paper shows the limitations of the compensation approach in modeling credible liabilities and explains the importance of relational credible commitments for ensuring sustainability and effectiveness of contracts. The author proposes an extended model of hostages in contracts using specific resources as a way of solving the “ugly princess” problem. Based on the specification of the temporal structure of contracting, we develop a game-theoretic model that takes into account the possibilities of opportunism on the part of both the pledger and the pledgee as an investor in specific assets. The study demonstrates the consequences of the wrong hostage chosen, as well as the characteristics of the interaction equilibrium due to the correct choice of it with an indication of the residual opportunism problem. The research provides a rationale why the promisee and the potential purchaser of full rights to an asset acting as a hostage are not always the same actor. The approaches to dealing with credible commitments in the context of renegotiations and multilateral contracts are outlined. The research results can serve as a basis for designing contracts requiring reciprocal collateral.